(untitled) (Cadernos de Sociomuseologia, 2022)
In the present edition of Cadernos de Sociomuseologia, we present debates on museums and sociomuseology that transit from the perspective of phenomenology. Analyzing its trajectory, much of museology, for a long time, sought to organize itself as a field that has its existence defined from its object, which has a restricted and self-centered existence in them. It was a museology that was defined by the museum, more concerned with infestations of insects or with humidity than with the society in which it was inserted. For a long time, however, this view has been questioned, in the direction of a more conscious and responsible concept of museology, whose main horizon is its social function and community participation is one of its premises. Recognizing these tectonic transformations for the field, it becomes necessary to seek new forms of analysis. The objective is, in this perspective, to expand the forms and possibilities. It is not, in most cases, to deny the trajectory of museology, but to see it reach inhospitable terrains, which can contribute to a constant increase in its performance. It is in this sense that studies based on phenomenology, as presented here, can represent a major impetus to the expansion of available knowledge. New interpretations, like many of the paths that the articles published here dare to tread, can, in this way, contribute so that museology and the museological work of people and institutions are increasingly aimed at a citizen practice, conscious and that has social aspirations. of different populations as a guideline.